Nonlinear adaptive speed and field weakening controllers for DC motors - Liu, Zuo Zong. (2008)
In this thesis, we address field weakening control of a SEDCM system for high performance speed tracking. Two control strategies, based on in-depth understanding of the physical system and drive characteristics, are proposed. They implement both the exact model knowledge controllers plus on-line parameter estimation, and the nonlinear adaptive MIMO controller. The exact model knowledge field weakening controllers are developed using differential geometric approach, model reference adaptive identification, and observer techniques. These controllers include 1) nonlinear MIMO controller, 2) improved nonlinear MIMO controller, 3) nonlinear load-adaptive MIMO controller, and 4) nonlinear sensorless MIMO controller. They are specially designed to fast reject load torque disturbance, which is a practically challenging problem for the closed-loop controller design of motor drives. The nonlinear adaptive MIMO field weakening controller is presented by backstepping technique combined with variable structure control design to compensate for the parametric uncertainties of the armature, field resistance, and load disturbance. Computer simulations of all these controllers and parameter estimation are presented for a specific motor to demonstrate their effectiveness.